Community Perception in the Use of "Songkok Recca" Hats based on Social Stratification - Yusriadi Yusriadi; Saidna Zulfiqar Bin-Tahir; Umi Farida; Geminastiti Sakkir; Zarina Akbar (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2019)
The use of the cap "Songkok Recca" is believed to have begun in the reign of the 31st Bone King named Andi Mappanyukki. The "Songkok Recca" hat used can show the social strata of the wearer. This study aims to look at public perceptions in the use of these hats associated with the social stratification of the Bugis community in Bone Regency. The study was conducted in Awangpone District, Bone Regency, South Sulawesi Province, using a qualitative approach, with a purposive sampling technique in determining informants. The method of collecting data using observation and interviews, with the number of informant’s as many as ten people. Data analysis techniques in this study are qualitative data analysis techniques. The results show that there a shift in the use of "Songkok Recca" hats today. In terms of social stratification, the use of the hat "Songkok Recca" no longer shows the degree of someone, but nowadays it is more described as a form of local wisdom of the Bugis community in Bone Regency.